International Congress for the study of the principles of a durable peace, Berne, 1916. The enforcement of peace - Taft, William H.; Central Organisation for a durable Peace (The Hague : Nijhoff, 1917)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: vredesinitiatieven; Wereldoorlog 1